KAJIAN DANA BAGI HASIL PAJAK DAN DANA ALOKASI KHUSUS TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI SULAWESI TENGAH. - Rika Suprapty (University of Riau Kepulauan, 2020)
AbstractThe aim of this study was to determine and analyze the Effect of Tax Revenue Sharing Funds, and Specific Allocation Funds on Gross Regional Domestic Product in Central Sulawesi Province. The type of data used is quantitative data. Data processing uses SPSS 18 program assistance. The results of the study show that (1) Tax Revenue Sharing Funds and Special Allocation Funds together have a positive and significant impact on Gross Regional Domestic Product in Central Sulawesi Province. (2) Tax-sharing fund has a positive but not significant effect on Gross Regional Domestic Product in Central Sulawesi Province (3) Special Allocation Fund has positive but not significant effect on Gross Regional Domestic Product in Central Sulawesi Province.